BUSINESS DEVELOPMENT STRATEGY USING SWOT ANALYSIS METHOD IN CULINARY INDUSTRY - Hasbullah, Hasbullah; Haekal, Jakfat; Prayogi, Pundi Rinti; Dian Eko A. , Dian Eko A. Prasetio (Journal of Industrial Engineering & Management Research, 2021)
Abstract: The culinary industry is increasingly growing in Indonesia. Data from the Indonesian Creative Economy Agency in 2016 shows that the culinary sub-sector contributes 41.4 % of the total contribution of the creative economy with a total value of IDR 922 trillion. This amount is the highest compared to the other 16 sub-sectors. This article presents a study on a merchant of modern contemporary food that has managed to sell 400 kg per month. The research objective is to provide the results of an assessment based on a SWOT (Strength Weakness Opportunity Analysis) to maintain and improve sales performance. The expected research contribution is a business strategy for small and medium enterprises (SME) in enhancing a sustainable business.